IMPLEMENTASI BUDAYA LITERASI PADA KEMANDIRIAN PESERTA DIDIK DI SD MUHAMMADIYAH SERUT BANTUL - Desy Ika Ratna Furi; Sugeng Riyanto (Universitas Ahmad Dahlan, 2019)
Literacy culture needs to be instilled early on, because it can foster students' interest in reading. Serut Muhammadiyah Elementary School is one of the schools implementing a literacy culture program. This study aims to explain the planning, implementation, evaluation of literacy culture programs at SD Muhammadiyah Serut, as well as describing the independence of students in literacy culture at SD Muhammadiyah Serut. This type of research uses descriptive research with a qualitative approach. The research subjects were school principals, class III teachers and class IV teachers, librarians, class III and IV students taken randomly. The objects in this study are all matters relating to the independence of students in literacy culture in SD Muhammadiyah Serut. Data collection techniques used include observation, interviews, and documentation. Data were analyzed using the Miles and Huberman models, while to test the validity of the data using source triangulation and technique triangulation. The results showed: that literacy program planning is related to the vision, mission and goals of the library, while the literacy culture has been running smoothly. Literacy cultural activities include reading iqra, reading Juz 'Amma, reading activities 15 minutes before the lesson begins, short story activities and bulletin classes. The next stage is the evaluation at Serut Muhammadiyah Elementary School conducted once a semester, to find out the extent of the literacy culture program. In the independence of students in the culture of literacy at Serut Muhammadiyah Elementary School as students do not read when the teacher does not ask. Then students are not confident when reading the results of their work.